Major elective abdominal surgery acutely impairs lower limb muscle pyruvate dehydrogenase complex activity and mitochondrial function. Issue 3 (March 2021) - Atkins, Ryan; Constantin-Teodosiu, Dumitru; Varadhan, Krishna K.; Constantin, Despina; Lobo, Dileep N.; Greenhaff, Paul L.
Summary: Background & aims: This post hoc study aimed to determine whether major elective abdominal surgery had any acute impact on mitochondrial pyruvate dehydrogenase complex (PDC) activity and maximal mitochondrial ATP production rates (MAPR) in a large muscle group (vastus lateralis -VL) distant to the site of surgical trauma. Methods: Fifteen patients undergoing major elective open abdominal surgery were studied. Muscle biopsies were obtained after the induction of anesthesia from the VL immediately before and after surgery for the determination of PDC and maximal MAPR (utilizing a variety of energy substrates). Results: Muscle PDC activity was reduced by >50% at the end of surgery compared with pre-surgery (p < 0.05). Muscle MAPR were comprehensively suppressed by surgery for the substrate combinations: glutamate + succinate; glutamate + malate; palmitoylcarnitine + malate; and pyruvate + malate (all p < 0.05), and could not be explained by a lower mitochondrial yield. Conclusions: PDC activity and mitochondrial ATP production capacity were acutely impaired in muscle distant to the site of surgical trauma. In keeping with the limited data available, we surmise these events resulted from the general anesthesia procedures employed and the surgery related trauma. These findings further the understanding of the acute dysregulation of mitochondrial function in muscle distant to the site of major surgical trauma in patients, and point to the combination of general anesthesia and trauma related inflammation as being drivers of muscle metabolic insult that warrants further investigation. Clinical trial registration: Registered at (NCT01134809).